Tom and Jerry [videorecording (DVD)] - Moretz, Chloë, 1997-; Peña, Michael, 1976-; Jost, Colin, 1982-; Delaney, Rob, 1977- (Warner Home Video, 2021)
When Jerry moves into a fine hotel on the eve of an important society wedding, the event planner hires Tom to get rid of him. Unfortunately, the battle which follows is big enough to destroy the wedding, her career, and possibly the hotel -- so the sworn enemies decide to work together to save it all.